Prevalence and Impact of Modifiable Risk Factors on Acute Coronary Syndrome: A Case Control Study - Anak Agung Ngurah Anindya Kusuma; I Gede Bagus Gita Pranata Putra (Cardiovascular and Cardiometabolic Journal (CCJ), 2024)
Highlights: 1. Smoking duration, dyslipidemia, hypertension, diabetes mellitus, obesity, and hyperuricemia, are significantly associated with ACS. 2. Obesity and hypertension are identified as risk factors for inpatient ACS. - Background: Acute coronary syndrome (ACS) is defined by the abrupt reduction or total obstruction of blood flow to the myocardium. Recognized risk factors for ACS include conditions such as hypertension, dyslipidemia, smoking, obesity, diabetes mellitus, hyperuricemia, as well as variables like age, gender, and family history of the ailment. The objective of this research was to examine the prevalence and importance of modifiable risk factors associated with ACS. Material and Methods: The study is structured as a prospective case-control study. The research sample comprises 100 ACS patients, categorized into three groups: STEMI, NSTEMI, and UAP. The Chi-Square test and logistic regression were used to examine the samples. The threshold for statistical significance was set at p<0.05. Results: ACS occurred more frequently in male patients (54%) and those aged â‰¥ 40 years (85%). Several factors demonstrated significant associations with ACS, including smoking habits, dyslipidemia, hypertension, diabetes mellitus, obesity, and hyperuricemia. Among these, inpatient ACS was notably linked with obesity (OR: 7.42; 95% CI: 1.48-37.11; p=0.015) and hypertension (OR: 0.13; 95% CI: 0.03-0.53; p=0.005). The presence of ACS was also correlated with a notable increase in inpatient care, with obesity and hypertension emerging as risk factors for inpatient ACS. Conclusion:  ACS was more common in males and individuals aged 40 or older, with significant associations identified between ACS and various factors, including smoking, dyslipidemia, diabetes, obesity, hyperuricemia, and hypertension, with obesity and hypertension specifically linked to inpatient ACS.